If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -11 = -14 Reorder the terms: -11 + 3x = -14 Solving -11 + 3x = -14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 3x = -14 + 11 Combine like terms: -11 + 11 = 0 0 + 3x = -14 + 11 3x = -14 + 11 Combine like terms: -14 + 11 = -3 3x = -3 Divide each side by '3'. x = -1 Simplifying x = -1
| -6Y+4(Y-7)=-18 | | -20-8n=-4(n+8) | | 10x+6(300-x)=2000 | | 7d^2+18b+8=0 | | 15x-31=9x+11 | | x^2+2y+14=0 | | 6(7a+2)=12-a | | 2(5w-1)=3w-4 | | 235x=200 | | 90x+15y-5x+3y+5= | | 6-(2-7k)=28+k | | -2x-4x+48=0 | | 0=2x^2-x+5 | | 3(x-3)-x=2x-9 | | 2-6x=9-8x-1 | | -8(7+3x)=4x | | 39z-22=39z+22 | | 5(v-5)=6v-19 | | (4x+4)(3x-3)=0 | | 210x=200 | | 103x-400=-215+872 | | (7x-7)=7 | | -2(4b-3)=16-3b | | -3s-4=14 | | 1800-380x=736-190x | | 3x^3-12x^2-28x+12=0 | | -2(-3n+3)-2n=-38-4n | | -8(7+3t)=4t | | 7y^2-30y+27=0 | | 1/5(2x-10)+4x=-3(1/5x+4) | | 0.5x^2-13x-0.6= | | 5c^2+2c-16=0 |